Culture-Supremacy: Expressions, Sources, and Resistance to a Psychology of Motivated Ignorance - Teo, Thomas (Research in the social scientific study of religion, 2022)
On the background of ethnocentrism, the lack of knowledge and experiences, and the a priori assumption that one’s culture is not only the standard or norm but at the apex of a historically constituted or imagined hierarchy, the expressions of culture-supremacy are discussed. Although culture-centrism afflicts every culture, with every context having a limited horizon as part of mainstream ideology, culture-supremacy entails reinforcing that status quo, using economic, military, ideological, practical, institutional, and academic power, and without knowing or caring about other cultures. It is argued that intersectionality is not only expressed in terms of oppression but also in terms of supremacy, reflecting the nexus between culture, race, religion, nationality, and country of origin, and that culture can easily become a substitute for biological discourses. Expressions and other phenomena of culture-supremacy and its motivated ignorance are discussed, as are its sources that include hierarchical thinking, quantification, and ranking. Culture-supremacy in the discipline of psychology is debated. Suggestions for combatting culture-supremacy, including the practices of solidarity and agape, are proposed, while it is emphasized that resistance cannot be reduced to individual activities and that it is equally important to work on interpersonal, societal, and economic conditions.